Propriedades mecânicas de juntas soldadas com diferença de espessura pelo processo de soldagem por atrito linear com mistura em ligas de Al-Mg para aplicação na construção naval - Feistauer, Eduardo Etzberger (2014)
The shipbuilding sector, as well as all modern transportation industries, is faced with demands for greater productivity while at the same time ensuring the manufacture of consistently high quality products, reducing levels of re-working, saving energy, and minimizing operational costs. Furthermore, it is imperative that new designs and all the stages of production comply with stringent environmental regulation. Within this context, the application of Friction Stir Welding (FSW) as a manufacturing process to weld Tailor Welded Blanks (TWB) for Al structures can contribute to the development of high speed craft and lightweight ships that are more fuel efficient, based on a high energetic efficient and environmental friendly welding process. In this work, the heterogeneous mechanical behavior of TWB joints welded by FSW was evaluated using quasi-static and cyclic loading, and the observed microstructural features were analyzed. The TWB joints were manufactured using dissimilar alloys and thicknesses (6 and 8mm) of particular interest in the shipbuilding sector (AA5083, AA5059 and AA6082). An evaluation of local constitutive properties in different regions through the TWB joint was performed by digital image correlation linked to the tensile test system. From the DIC data processing were generated stress concentrations diagrams and true stress-strain curves for several TWB subzones. The DIC methodology used as well as the accuracy of the proposed method are described in detail. The joints exhibited excellent mechanical properties approximately the same as those of the base metal for the joints manufactured with work hardened alloys (AA5059/AA5083) and 76% mechanical efficiency to those manufactured with the heat-treatable alloy (AA6082). The fatigue strength of the TWB joints were higher than the IIW references for welded structures in aluminum and the fracture mechanisms were characterized using SEM.